Efektivitas Pelatihan Komunikasi Aktif terhadap peningkatan keterampilan kepemimpinan di Perusahan x Surabaya - Lubis, Syahmardan; Rini, Amanda (Indonesian Journal Publisher, 2025)
This study aims to evaluate the effectiveness of active communication training in improving leadership skills among supervisors at Perusahan x Surabaya. The main issue addressed in this organization involves communication barriers between superiors and subordinates, which negatively impact coordination and work motivation. A mixed-methods approach was employed involving 50 participants from the Security and Order Division. Data were collected through interviews, observations, and pre-test and post-test assessments, and analyzed using a paired sample t-test. The results revealed a significant improvement in communication skills after the training, with a value of t = -20.642 and p = 0.000 (p < 0.05). Participants showed enhanced active listening, message clarity, and decision-making transparency. The training effectively strengthened workplace relationships, improved motivation, and fostered a two-way communication culture within the organization.